EXPLORING THE ROLE OF FAMILY FUNCTIONING AND ONLINE SOCIAL INTERACTION IN THE DEVELOPMENT OF DEPRESSION AND ANXIETY AMONG GEN ZS - Akinwale, Gbenusola Abike; Adejinle, Patrick (African Journal of Social and Behavioural Sciences, 2024)
This study examined family functioning and online social interaction (social media) as predictors of depression and anxiety among the Gen Z developmental cohort at the University of Lagos. The study adopted a cross-sectional survey design. The study selected (320) participants across the University of Lagos in Lagos State with the use of a convenient sampling method. Four Hypotheses generated were tested using multiple regression analysis. The results revealed that family functioning had an insignificant positive relationship with depression and anxiety (F (7,65) = 0.042, p=0.09) < There was a significant relationship between online social interaction [R2 = .000, F (1, 409) = .073, p> .787) and depression and anxiety. Family functioning and online social interaction significantly predicted depression and anxiety in the Gen Z group (R2 = .069, F (6.633) =.196). The study concluded that there is a complex interplay between family functioning, social media use and the mental well-being of Generation Z (Gen Z). The findings indicate that a high level of family functioning characterized by effective communication and emotional support was not linked to a high level of depression or anxiety among individuals in the GenZ. The study recommended a good family relationship to promote healthy living among adolescents especially those in the GenZ developmental age cohort because of their exposure to social media.